General comments stimulated by three articles on fire behaviour of bridges in the journal of constructional steel research. (June 2023) - Chow, W.K.; Chow, C.L.; Cheng, C.H.
Highlights: Comments stimulated by three articles on fire behaviour of bridges were presented. Consequences of a bridge fire or explosion under a traffic jam can be very hazardous. Fire resistance period for bridges should be determined from a standardized scenario.